2011
DOI: 10.1093/jb/mvr037
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IGF-1/PI3K/Akt signalling by the phosphoinositide phosphatase pharbin

Abstract: Pharbin, a 5-phosphatase that induces arborization, is one of the phosphoinositide 5-phosphatases that is highly mutated in patients with Joubert syndrome. Pharbin can hydrolyse PI(4,5)P(2) and PI(3,4,5)P(3) and has the same substrate specificity as SHIP2 and SKIP, which negatively regulate PI3K signalling. Here, we investigated the role of pharbin in IGF-1/PI3K signalling. Ectopic expression of pharbin markedly suppressed the IGF-1-induced activation of Akt without affecting p42/44 MAP kinase phosphorylation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Further, we confirmed that INPP5E siRNAs did not impact MAD2 (data not shown), whose transcript is sensitive to nonspecific siRNA silencing (34). INPP5E overexpression caused cellular toxicity, as described before (references 6 and 35 and data not shown). Consistent with its role in cell division, INPP5E accumulates as cells progress through interphase toward mitosis (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Further, we confirmed that INPP5E siRNAs did not impact MAD2 (data not shown), whose transcript is sensitive to nonspecific siRNA silencing (34). INPP5E overexpression caused cellular toxicity, as described before (references 6 and 35 and data not shown). Consistent with its role in cell division, INPP5E accumulates as cells progress through interphase toward mitosis (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…INPP5E dephosphorylates at the 5-position PtdIns(3,4,5)P 3 ( 159,177,178 ), PtdIns(4,5)P 2 ( 159,178,179 ), and PtdIns(3,5)P 2 ( 177 ) in vitro. In contrast, other reports have suggested that neither PtdIns(4,5) P 2 ( 177 ) nor PtdIns(3,5)P 2 ( 178 ) are substrates for INPP5E in vitro. Furthermore, it has been reported that Ins(1,4,5) P 3 and Ins(1,3,4,5)P 4 can be dephosphorylated by INPP5E ( 179 ); however, other studies have shown they are not substrates ( 159,177 ).…”
Section: Phosphoinositide 4-phosphatase Activities and Cancermentioning
confidence: 99%
“…INPP5E is widely expressed, with the greatest expression detected in the heart, testis, and brain ( 159,177 ). INPP5E dephosphorylates at the 5-position PtdIns(3,4,5)P 3 ( 159,177,178 ), PtdIns(4,5)P 2 ( 159,178,179 ), and PtdIns(3,5)P 2 ( 177 ) in vitro. In contrast, other reports have suggested that neither PtdIns(4,5) P 2 ( 177 ) nor PtdIns(3,5)P 2 ( 178 ) are substrates for INPP5E in vitro.…”
Section: Phosphoinositide 4-phosphatase Activities and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…82 Indeed, Inpp5E participates in growth factor signaling, primarily controlling hypothalamic responses to insulin stimulation. 82,84,98 It helps regulate basal levels of PI(3,4,5)P 3 in the hypothalamus, the main central nervous system (CNS) regulator of insulin signaling. 82 Inpp5E is abundantly expressed in the hypothalamus and is tyrosine phosphorylated by activated insulin receptor.…”
Section: Insulin Signaling and Glucose Homeostasismentioning
confidence: 99%